Study of Different Recycling Approaches for Gypsum-Based Composites with Recycled Rubber Aggregates - Daniel Ferrández; Alicia Zaragoza-Benzal; Evangelina Atanes-Sánchez; Beatriz Merillas; Ricardo Mateus; Paulo Santos (Buildings)
The worldwide demand for gypsum resources is continuously growing due to its versatility in the building industry. In this context, incorporating recycled aggregates is gaining attention for enhancing the physico-mechanical properties of gypsum-based composites. Recycled rubber aggregates have stood out in recent decades as a common option in the development of prefabricated panels and sheets. This study presents a design of gypsum-based composites in which 20 to 40% of the volume of the binding material has been replaced with recycled rubber in two different formats: granulates (1.0–2.5 mm) and powder (<0.8 mm). Three series of composites have been developed to explore their recyclability: Series 1, recycled rubber aggregates and commercial gypsum; Series 2, recycled rubber aggregates (by trituration of samples from Series 1) and commercial gypsum; and Series 3, 100% recycled gypsum and rubber aggregates. All the composites surpass the minimum values of flexural and compressive strength (1 and 2 MPa, respectively) indicated by the normative result. Furthermore, the physicochemical characterisation showed the effectiveness of the recycling process of the triturated dihydrate for obtaining the hemihydrate. A study of the environmental impact revealed a 60% reduction in CO2 emissions, the equivalent of producing 1 m2 of prefabricated board using traditional gypsum. Therefore, this research outlines the potential of gypsum recycling with recycled rubber aggregates, thus promoting the circularity of construction products and decreasing the building’s environmental footprint. This represents a novelty compared to current studies, which are more oriented towards recycling and recovery of waste from conventional plasterboards.